PENGARUH PENINGKATAN JUMLAH WISATAWAN TIONGKOK KE KOREA SELATAN TERHADAP PEREKONOMIAN KOREA SELATAN - Bangun, Johandy Rendicky Vinandra; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this study is to determine the effect of the increase in the number ofChinese tourists in the South Korean economy through a series of international economicpoliticalrelations conducted by both parties in various sectors, especially tourism.This research uses liberalism perspectives. This perspective is an economic systemin which the market is an autonomous scope of society that runs in accordance with itseconomic laws. Economic exchange is a positive sum-game (everyone gets more profit thanthey expect). The market will tend to maximize its profits for all individuals and companiesparticipating in the market. Liberal economy is a space of cooperation for mutual interests,both between countries and between individuals.Tourism is an activity that has grown by about 25 percent in the last 10 years. Itcurrently accounts for about 10 percent of the world's economic activity and is one of themain generators of labor. The rise of Chinese tourists has affected South Korea's economicdevelopment. This can be seen from the increasing number of exports and imports, thecountry's foreign exchange reserves and the income per capita of South Korea.Keywords : Tourism, Liberalism, State Reserves